2016
DOI: 10.4085/1062-6050-51.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Graduate-Assistant Athletic Trainers' Perceptions of the Supervisor's Role in Professional Socialization: Part II

Abstract: Context: Many new athletic trainers (ATs) obtain graduate-assistant (GA) positions to gain more experience and professional development while being mentored by a veteran AT; however, GA ATs' perceptions of the supervisor's role in professional development are unknown. Objective: To explore the supervisor's role in the professional development of GAs in the collegiate setting. Design: Qualitative study. Setting: Phone interviews. Patients or Other Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…This is consistent with how GAs in the collegiate setting view their mentors. 46 No formal mentoring or transition-to-practice programs have been reported in the athletic training literature, to our knowledge, but formal transition-to-practice programs have been investigated 8,11,19,47 in nursing. One common component of these programs is providing new nurses with a resource person, often called a mentor or preceptor.…”
Section: Mentoringmentioning
confidence: 99%
“…This is consistent with how GAs in the collegiate setting view their mentors. 46 No formal mentoring or transition-to-practice programs have been reported in the athletic training literature, to our knowledge, but formal transition-to-practice programs have been investigated 8,11,19,47 in nursing. One common component of these programs is providing new nurses with a resource person, often called a mentor or preceptor.…”
Section: Mentoringmentioning
confidence: 99%
“…We developed the survey using results from interviews with supervisors of newly credentialed ATs, 11 interviews with GA ATs, 12,13 and the previous literature 22 examining the transition to practice of medical students. The survey was part of a larger instrument that also examined orientations provided to newly credentialed ATs.…”
Section: Instrumentationmentioning
confidence: 99%
“…10 Often, the graduate assistantship is used as a formal mode of transitioning newly credentialed ATs into practice, allowing new ATs to gain independent practice experience while being mentored and supported by an experienced AT. 8,[11][12][13] Transition to practice has been widely studied in nursing and is gaining more recognition in athletic training research 1,[5][6][7][8][9][14][15][16][17][18][19][20][21] ; however, many of these studies were qualitative in nature. Although some of the challenges and feelings associated with this transition have been ex-plored, 1,21 how specific characteristics, such as the employment setting, type of professional program, or job title, affect the newly credentialed AT's feelings during transition to practice is unknown.…”
mentioning
confidence: 99%
“…Supervisors and other staff members can also provide support to the new ATs, which can help the latter become involved in the organizational culture and develop self-efficacy. 29, 43 Pitney et al 37 observed that finding stability within an organization was related to collegiality, administrative support, and alignment of organizational values with the AT's values. Supervisors can begin employment for new ATs by outlining the organization's values along with role expectations to ensure congruence with their values.…”
Section: Orientation Tacticsmentioning
confidence: 99%
“…A mentor is a valuable resource for a new AT transitioning into his or her role. 2,29,43 Although some orientation tactics received higher mean values than others, nearly all of the tactics were at least minimally useful; therefore, supervisors should consider all of these tactics when designing the orientation process. Supervisors should also provide resources, such as an EAP, policies and procedures manual, and outline of various protocols.…”
Section: Suggestions For Orientationmentioning
confidence: 99%